A case report of paroxysmal dystonic choreoathetosis due to hypoglycaemia induced by an insulinoma. Issue 2 (August 1996) - Shaw, C; Haas, L; Miller, D; Delahunt, J
Abstract : Hypoglycaemia due to an insulinoma can mimic acute disorders of cognition, consciousness, epilepsy, transient ischaemia, or psychosis, and chronic disorders of dementia and neuropathy. Misdiagnosis and delay in treatment are common and prolonged hypoglycaemia can lead to permanent neurological deficit or fatal coma. A 27 year old woman with hypoglycaemia induced by an insulinoma presented with features typical of paroxysmal non-kinesiogenic dystonic choreoathetosis. Striatal dysfunction as a consequence of hypoglycaemia has rarely been described. Insulinoma is a readily treatable condition that should be considered in the differential diagnosis of a paroxysmal movement disorder.